2018
DOI: 10.1080/20009666.2018.1424485
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant melanoma of the lung: a case report of a rare tumor and review of the literature

Abstract: Primary malignant melanoma of the lung (PMML) is a rare malignancy that exhibits aggressive behavior and has a very poor prognosis. We are reporting on a case of PMML in an otherwise healthy 22-year-old Caucasian male with no significant past medical history and an unremarkable family history. The patient initially presented with a 2-month history of a cough and an unexplained 22-lb weight loss. His initial chest X-ray demonstrated opacification of the right lower lobe (RLL) of his lung and a subsequent comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Endobronchial lesions are present in the tumors, causing cough, hemoptysis, and pulmonary atelectasis (4). However, its pathogenesis is still debated, with some researchers (5) suggesting that melanocytes migrate to the respiratory tract during embryogenesis, where they transform into cancer cells. Other researchers hypothesized…”
Section: Discussionmentioning
confidence: 99%
“…Endobronchial lesions are present in the tumors, causing cough, hemoptysis, and pulmonary atelectasis (4). However, its pathogenesis is still debated, with some researchers (5) suggesting that melanocytes migrate to the respiratory tract during embryogenesis, where they transform into cancer cells. Other researchers hypothesized…”
Section: Discussionmentioning
confidence: 99%
“…Primary melanoma of the lung (PPM) is extremely rare, accounting for only 0.4% of MM; it is usually endobronchial and exhibits symptoms such as cough, hemoptysis, post-obstructive pneumonia, lobar collapse, atelectasis, weight loss, and fatigue [ 6 ]. Up to 30% are diagnosed as incidental findings, being asymptomatic at the time of diagnosis [ 7 ]. Lymph node involvement is found in 40% of patients; in the case presented here, the patient had no positive nodes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, younger PMML survivors were rarely seen. Recently, Yunce et al [21] reported a resection in a 22-year-old Caucasian. In our case, the PMML patient was a 57-year-old who succumbed to the disease 1 month after operation.…”
Section: Discussionmentioning
confidence: 99%